2003
DOI: 10.1242/jcs.00756
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of caspase activation and a requirement for NF-κB function in theToxoplasma gondii-mediated blockade of host apoptosis

Abstract: Mammalian cells infected with the protozoan parasite Toxoplasma gondii are resistant to many apoptotic stimuli transmitted along both the mitochondrial and death receptor pathways. Apoptosis, and its inhibition in infected cells, was examined using multiple morphological, molecular and biochemical approaches. The data strongly indicate manipulation of the host apoptotic machinery at multiple levels, focusing on the inhibition of host caspases. Activation of the pro-apoptotic caspase family of proteases is a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 81 publications
4
156
1
5
Order By: Relevance
“…Usually, cells infected with T. gondii present inactive caspases 3, 8 and 9, but activities of these caspases were detected in p65 −/− cells harbouring T. gondii. Consequently, upregulated expression of Bcl-2 family proteins and c-IAPs, usually observed following infection, is not seen in p65 deficient cells [104]. This observation demonstrated the importance of NF-κB p65 component as a key factor in the protection of the infected fibroblast against apoptosis [99].…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 93%
See 1 more Smart Citation
“…Usually, cells infected with T. gondii present inactive caspases 3, 8 and 9, but activities of these caspases were detected in p65 −/− cells harbouring T. gondii. Consequently, upregulated expression of Bcl-2 family proteins and c-IAPs, usually observed following infection, is not seen in p65 deficient cells [104]. This observation demonstrated the importance of NF-κB p65 component as a key factor in the protection of the infected fibroblast against apoptosis [99].…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 93%
“…NF-κB members P50 (NFκB1), p65 (RelA), p52 (NFκB2) and RelB are found in nuclear extracts of T. gondii infected fibroblasts [99]. Additionally, infection with T. gondii does not protect host fibroblasts deficient in p65 in the presence of inducers of the mitochondrial or death receptor apoptotic pathways [104]. Usually, cells infected with T. gondii present inactive caspases 3, 8 and 9, but activities of these caspases were detected in p65 −/− cells harbouring T. gondii.…”
Section: Role Of the Nf-κb Pathwaymentioning
confidence: 99%
“…These reporter cell lines were established to allow for a rapid screening of mutants of the Toxoplasma gondii parasites defective in activating NF-κB in the host cells. We have previously shown that T. gondii inhibits apoptosis in an NF-κB dependent manner in host fibroblasts [20,24]. A stable NF-κB-GFP reporter cell line (PHS2) previously developed in our lab for screening of mutants of the T. gondii, lost its response to NF-κB activation over time, despite repeated selection of positive clones (data not shown).…”
Section: Gfp Reporter Responds Differently To Different Nf-κb Stimulimentioning
confidence: 94%
“…T.gondii is an obligate intracellular parasite that can infect any warm blood animal [27] and is known to manipulate multiple intracellular signaling pathways of the host. One of those is the NF-κB pathway, whose activation is required for inhibition of host apoptosis [24]. We have previously shown that activation of NF-κB is partially achieved by phosphorylation of a subset of host IκBα [21].…”
Section: Introductionmentioning
confidence: 99%
“…The prediction obtained as a network shows that the Leishmania parasite activates NF-KB via the PI3K/Akt, leading eventually to the transcriptional repression of iNOS [69]. In addition, activation of the transcription of NF-kb seems to be crucial in protecting against apoptosis of cells infected with intracellular pathogens [64], [70]- [72]. On the other hand, NF-kb induced IRF-1 activation (figure :9) [73].…”
Section: B Cytoscapementioning
confidence: 97%